TORACOBIFEMORAL BYPASS IN A PATIENT WHO UNDERWENT REPEATED INTERVENTIONS ON THE AORTO-FEMORAL SEGMENT DUE TO ATHEROSCLEROTIC LESIONS - Andrey E. Zotikov; Evgeny G. Myltsev; Irina E. Timina; Vladimir A. Kulbak; Alexander l. Golovyuk; Anzhelika V. Kozhanova (Атеротромбоз)
Aortobifemoral bypass is still the gold standard treatment in surgery of the aortofemoral segment. The 1980s – 1990s classic publications showed that primary patency ranges from 76–95% in 5 years, and 75–85% in 10-years [1, 2]. Thrombosis of both branches of the bifurcation prosthesis occurs in 1–4% of patients. These patients may undergo thrombectomy with reconstruction of the distal anastomoses, re-aortofemoral prosthetics and, finally, extraanatomic bypass surgery.